Current Account Sustainability in Brazil A Non-Linear Approach - de Mello, Luiz (OECD Economics Department Working Papers, 2009)
The possibility that a country's external current account may adjust nonlinearly to shocks is attracting increasing attention in the empirical literature. To shed further light on this issue in the context of emerging-market economies, this paper uses Brazilian data to estimate the determinants of the current account in a smooth-transition vector-autoregressive (ST-VAR) setting. We allow for the transition parameters and the model coefficients to be estimated simultaneously by non-linear constrained maximum likelihood. We find strong evidence of non-linearity in the VAR when (lagged) government consumption and investment are used as the variables governing transition across regimes. The computation of non-linear impulse response functions suggests that the system's history, as well as the sign and magnitude of shocks, affect the current account's responses to exogenous changes in income, government consumption and investment. In particular, responses to fiscal shocks depend on whether they are positive or negative and whether they follow periods of fiscal expansions or contractions. Current account responses to a positive fiscal impulse are much stronger when conditioned on periods of fiscal expansion (rising government consumption) than retrenchment. The importance of conditioning history and the magnitude of shocks in the current account's response to shocks is confirmed by forecast error variance decomposition analysis